The role of informal learning in the professionaldevelopment of kindergarten teachers (Training and Practice : Journal of Educational Sciences, 2021)
In a dynamically developing, knowledge-based society, not only the forms of learning but also the places of learning are changing, and the role of the workplace in learning has also increased. The changing work environment, along with the development of information and communication technologies, has made telecommuting possible, among other things, significantly transforming the way we work and interact atwork. Several studies have focused on what factors within an organization support or hinder workplace learning. For today's economic competitiveness, it is no longer enough to possess knowledge, but the learning capacity of organizations has become decisive. Not only the individual, but also the ability of organizations to adapt quickly to the constantly changing circumstances around them (Halász, 2009).